COOPERATIVE LEARNING FOR ENHANCING EFL LEARNERS' SPEAKING SKILL - Kurnia Febianti; Sri Wahyuni (Universitas PGRI Palembang, 2022)
Students’ low motivation and anxiety are common problem faced by the English teachers in teaching English as foreignlanguage, therefore, think pair and share as one of cooperative learning approach can be applied in solving those problem. The objective of the study was to find out the difference of students’ speaking skill who were taught by using Think Pair and Share and those who were not. The method that was used in this study was quasi experimental design. The population and sample of this study was the eight grader of SMP N 1 PajarBulan. The data were collected by using pre-test and post-test. The result of the study showed that there was significant result of students’ speaking skill after being taught by using Think Pair and Share. It can be proved by comparing the result of the t-table and t-obtained. The statistical result showed that t-obtained was higher than t-table. So, it can be said that Think Pair Share can be used in improving students’ speaking skill.